International Journal Reputation Enhancement Training: Effectiveness And Implications Analysis Case Study At Higher Education Institutions In Indonesia, Somaliland, and Syria - Mukit, Abdul; Al-Ansi, Abdussalam Hamoud Ghalib; Mulyana, Yana; Zulkiflih, Zulkiflih; Madani, Mohammad Thoyyib; Wahidin, Unang; Hamdy, Mohammad Zainal; Rufaida, Rifki (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2024)
The international training program titled "International Journal Reputation Enhancement Training: Effectiveness and Implications Analysis, Case Study at Higher Education Institutions in Indonesia, Somaliland, and Syria" aims to enhance the capacity for scholarly writing and international publication at higher education institutions in three countries. The program is conducted in several stages, beginning with initial preparation from August 3 to August 24, 2024, followed by a theoretical session on August 24, 2024, manuscript preparation on August 27, and manuscript publication on September 9, 2024. The training methodology involves meticulous planning, interactive teaching, direct guidance in manuscript writing, and final evaluation. This training is designed to provide participants with in-depth knowledge of international journal standards and effective scholarly writing techniques. During the theoretical session, participants are introduced to key concepts and interactive teaching methods to ensure a comprehensive understanding. Subsequently, participants receive guidance in preparing and aligning their manuscripts with international journal templates. The published manuscripts are assessed to ensure quality and compliance with academic standards. Evaluation is conducted to assess the effectiveness of the training and its impact on participants' publication capabilities. The evaluation results demonstrate significant improvements in manuscript quality and international publication opportunities, providing insights for future enhancements. This training successfully achieved its objectives by improving participants' scholarly writing skills and strengthening the academic reputation of their institutions.